2015
DOI: 10.1371/journal.pone.0143946
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Evaluation of a Parenting Resilience Elements Questionnaire (PREQ) Measuring Resiliency in Rearing Children with Developmental Disorders

Abstract: We developed a parenting resilience elements questionnaire (PREQ) measuring the degree to which mothers possess elements that aid in adapting to challenges and difficulties related to children with developmental disorders (DD). A total of 424 parents of children with DD were recruited from five medical institutes. Psychometric properties of PREQ were evaluated using data of 363 mothers of children with DD. Furthermore, multiple regression analysis was performed, predicting depressive symptoms and parenting beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
(44 reference statements)
2
26
0
1
Order By: Relevance
“…The prevalence of depression among the parents participating in the present survey was 45.2%. That is high compared with 32.7% observed in a previous study in Japan [ 43 ], and is similar to the 48.6% found in an Oman study [ 44 ]. The differences may be accounted for by the fact that the present study and the one conducted in Oman [ 44 ] focused on parents of children with ASD; the earlier study in Japan [ 43 ] examined parents of children with various developmental disabilities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of depression among the parents participating in the present survey was 45.2%. That is high compared with 32.7% observed in a previous study in Japan [ 43 ], and is similar to the 48.6% found in an Oman study [ 44 ]. The differences may be accounted for by the fact that the present study and the one conducted in Oman [ 44 ] focused on parents of children with ASD; the earlier study in Japan [ 43 ] examined parents of children with various developmental disabilities.…”
Section: Discussionsupporting
confidence: 89%
“…That is high compared with 32.7% observed in a previous study in Japan [ 43 ], and is similar to the 48.6% found in an Oman study [ 44 ]. The differences may be accounted for by the fact that the present study and the one conducted in Oman [ 44 ] focused on parents of children with ASD; the earlier study in Japan [ 43 ] examined parents of children with various developmental disabilities. One investigation [ 45 ] reported that parents of children with ASD suffer more from depression than parents of children with other developmental disabilities.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, when parent perception of their own parenting was present in the models, the relationship of PS and parent MHP with child EBP became non-significant in three (Bader et al 2015 ; Falk et al 2014 ; Hastings and Brown 2002 ) out of four studies. Only in the largest study did both child EBP and parent perception of their own parenting both appear to contribute significantly to parent MHP (Suzuki et al 2015 ). Parents’ perception of their ability to parent effectively is therefore a plausible candidate for a mediator of the relationship between child EBP and parent psychological distress variables.…”
Section: Resultsmentioning
confidence: 99%
“… (int.) HSCL .37 (45) .50 (45) 4, 5 6 Suzuki et al ( 2015 ) 405; clinic NR .69; clinical 10.2 (3.5), 3–18 1.00 41.6 (5.4), 28–54 Japanese SDQ Japanese GHQ-12 .22 (313) 4 Taylor and Warren ( 2012 ) 75; clinic .88 1.00; research 5.1 a (NR), NR 1.00 NR CBCL (ext.) (int.)…”
Section: Methodsmentioning
confidence: 99%
“…Parenting Resilience Elements Questionnaire (PREQ) (for parents/guardians) PREQ [40] measures the degree to which mothers possess elements that aid in adapting to challenges and difficulties related to children with developmental disorders. It comprises 29 items and three factors, namely, "knowledge of the child's characteristics, " "perceived social supports," and "positive perceptions…”
Section: Cbt Followupmentioning
confidence: 99%